Bayesian hierarchical stock–recruitment models for setting conservation limits for Atlantic salmon stocks in Scotland - James P. Ounsley; Nora N. Hanson; Gordon W. Smith; Jonathan P. Gillson; Brian A. Shields; Stuart J. Middlemas (Journal of Fish Biology, 2026)
Atlantic salmon ( Salmo salar L.) populations in Scotland are subject to active management and conservation practices which require biological reference points (BRPs), specifically conservation limits, defined at the level of the stock. Acquiring the data necessary to independently derive these BRPs for all managed populations in Scotland is prohibitive, motivating the use of Bayesian hierarchical stock–recruitment models. These models provide a framework for the joint analysis of multiple monitored stocks, and the transportation of BRPs to non‐monitored stocks. This framework was adapted to introduce nationally relevant and available covariates that might explain variation in recruitment dynamics among stocks and reduce uncertainty in posterior predictions of BRPs. Model selection was designed to maximise the prediction of BRPs for new stocks via leave‐one‐group‐out cross‐validation. Out‐of‐sample predictive performance was maximised by including information on latitude, land usage within the catchment and historic catch per area of salmon habitat in the model. The extensions to Bayesian hierarchical stock–recruitment methods presented here, when applied at a national scale, result in more locally discriminative posterior predictions compared to existing methods and are readily applicable to other stocks and species.

Correction to: The attribution of human health outcomes to climate change: transdisciplinary practical guidance - K. L. Ebi; A. Haines; R. F. S. Andrade; C. Åström; M. L. Barreto; A. Bonell; K. Bowen; N. Brink; C. Caminade; C. J. Carlson; R. Carter; P. Chua; et al. (Climatic Change, 2026)

The attribution of human health outcomes to climate change: transdisciplinary practical guidance - K. L. Ebi; A. Haines; R. F. S. Andrade; C. Åström; M. L. Barreto; A. Bonell; K. Bowen; N. Brink; C. Caminade; C. J. Carlson; R. Carter; P. Chua; et al. (Climatic Change, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Evaluation of ballistics euthanasia applied to stranded cetaceans using ethological and post-mortem computed tomography assessment - Rebecca M. Boys; Brian C. W. Kot; Gordon Lye; Ngaio J. Beausoleil; Stuart Hunter; Karen A. Stockin (Veterinary Research Communications, 2024)
Debilitated stranded cetaceans with low survival likelihood, may require euthanasia to avoid further suffering. Euthanasia can involve chemical or physical methods, including ballistics. Ballistics should cause instantaneous, permanent insensibility through brainstem disruption. Despite wide application, there is limited understanding of ballistics-related welfare outcomes. We opportunistically examined behaviour of three maternally-dependent cetaceans following shooting and the related cranial disruption post-mortem using computed tomography (PMCT). Our aim was to understand whether a ‘humane death’, i.e., euthanasia, was achieved. Each animal was shot using different projectile types: soft non-bonded, solid, and soft bonded. In two animals, insensibility was not immediately assessed following shooting, although both were reported as ‘instantaneously insensible’. From our analysis, all animals displayed musculoskeletal responses to shooting, including peduncle stiffening and slack lower jaw, followed by musculature relaxation 24-, 10.3- and 20.8-seconds post-ballistics, respectively. The animal shot with a soft non-bonded projectile also displayed agonal convulsions and tail-lifting for 16-seconds post-shot; these were not observed for solid or soft bonded projectiles. PMCT findings indicated projectile disruption to the brainstem and/or spinal cord likely to cause near-instantaneous insensibility. However, extra-cranial wounding was also evident for the soft non-bonded projectile, highlighting potential for additional welfare compromise. Our results demonstrate that ballistics can achieve a relatively rapid death in young, stranded cetaceans, but careful equipment selection is required. To ensure a humane death, verification of insensibility must be undertaken immediately following shooting. Further studies should be undertaken to improve knowledge of appropriate procedures and equipment for euthanasia, ensuring humane deaths for compromised cetaceans.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Precision and accuracy of Dahl‐Lea back‐calculated smolt lengths from adult scales of Atlantic salmon Salmo salar - Nora N. Hanson; Gordon W. Smith; Stuart J. Middlemas; Christopher D. Todd (Journal of Fish Biology, 2019)
Using tagged and recaptured Atlantic salmon Salmo salar (n = 106) the present analysis shows that the most commonly applied linear back‐calculation method for estimating past length, the Dahl‐Lea method, resulted in overestimation of the length of large smolts and underestimation of small smolts. A correction equation ( y = 0.53 x + 6.23) for estimating true smolt length ( y ) from lengths back‐calculated from adult scale measures ( x ) to account for these systematic discrepancies is proposed.

Twenty-Five Years of the Clean Water Act: How Clean Are Forest Practices? - George G. Ice; Gordon W. Stuart; Jack B. Waide; Lloyd C. Irland; Paul V. Ellefson (Journal of Forestry, 1997)